Inpatient usage of faecal calprotectin in a tertiary hospital. Issue 3 (20th March 2022) - Barnes, Alex; Spizzo, Paul; Mountifield, Réme
Abstract: Background: Faecal calprotectin (FCP) is a highly sensitive non‐invasive marker of intestinal inflammation that has evidence‐based roles in outpatient diagnosis and management of inflammatory bowel disease. Aims: To examine indications for FCP in a tertiary inpatient population and its role in inpatient management and subsequent investigations. Methods: An electronic database was used to identify all patients over the age of 18 years who had FCP performed during a hospital admission over a 3‐year period from March 2016 to the end of March 2019. Electronic records and case notes were reviewed with follow up to March 2020, seeking indication for testing, healthcare units requesting, and subsequent investigations and treatment resulting from FCP. Results: Over a 3‐year period, 111 FCP inpatient results were identified. There were three changes in management based on the FCP result that led to further investigations that did not lead to any clinically significant pathology. There was no observable difference in the number of colonoscopies performed based on FCP level. The numerical FCP value was associated with clinically significant findings on colonoscopy. Negative predictive value of FCP level (≤50 μg/g) for clinically significant finding on colonoscopy was 64%. Conclusion: Non‐guideline‐based hospital inpatient usage of FCP rarely changes inpatient management and had no observable difference in the usage of subsequent diagnostic colonoscopy. Regardless, the FCP level remained a strong predictor of clinically significant pathology on colonoscopy.